Analysis of the relative age effect in elite wrestlers - Latyshev, M.; Tropin, Y.; Podrigalo, L.; Boychenko, N. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. The relative age effect has been used to refer to the age differences between individuals who have been grouped together in a sports competition. In this sense, the relative age effect is considered a determining factor of sporting success. Problem and Aim. Determine the influence of relative age on the achievement of success by athletes in top-level competitions in modern wrestling. Methods and materials. In the research paper, the data of the athletes (n = 682) who took from 1 to 8 places at the 2017, 2018 and 2019 World Championships and the 2016 Olympic Games in Greco-Roman and freestyle wrestling are considered. The athletes were sub-categorized by the athletes` dates of birth; medalists; participation and achieved success in the cadets and juniors competitions. Results. There are more athletes who were born in the first half of the year than in the second: 54.7% versus 45.3%, respectively. The distribution of medal winners by date of birth is as follows: it turned out that 53.3% of medalists were born in the first half of the year while 46.7% - in the second half of the year (p>0.05). Conclusion. The data obtained show that the relative age effect does not affect the achievement of success in wrestling and is leveled at the adult stage. However, the analysis has shown that the greatest influence of the relative age effect on athletes was revealed at the cadet level.